Penerapan media visual dalam pembelajaran IPAS untuk meningkatkan hasil belajar peserta didik sekolah dasar - Dzulhijatul Awalin Zuroida; Ika Santia; Tanto Hermawan (Jurnal Pendidikan Dasar, 2025)
This classroom action research investigates the efficacy of visual media in enhancing Integrated Science and Social Studies (IPAS) learning among fourth-grade s tudents at SDN Banjaran 4, Kediri. Implemented across two cycles (February 2025), the study employed animated videos (Cycle I) and culturally contextualized 3D dioramas (Cycle II) to address identified learning gaps - diagnostic tests revealed 72% of students struggled with abstract concepts. Quantitative results demonstrated significant progress, with mean scores increasing from 58.6 (pre-test) to 74.2 (Cycle I) and 82.4 (Cycle II), while observational data showed an 85% boost in engagement. Qualitative analysis revealed improved conceptual mastery and classroom participation. The large effect size (Cohen's d = 1.24) substantiates visual media's effectiveness in facilitating concrete-to-abstract knowledge transitions, particularly for learners at Piaget's concrete operational stage. These findings underscore the pedagogical value of tailored visual aids in elementary IPAS instruction.